Immunosuppressive PLGA TGF-β1 Microparticles Induce Polyclonal and Antigen-Specific Regulatory T Cells for Local Immunomodulation of Allogeneic Islet Transplants - Li, Ying; Frei, Anthony W.; Labrada, Irayme M.; Rong, Yanan; Liang, Jia-Pu; Samojlik, Magdalena M.; Sun, Chuqiao; Barash, Steven; Keselowsky, Benjamin G.; Bayer, Allison L.; Stabler, Cherie L. (Frontiers in Immunology, 2021)
Allogeneic islet transplantation is a promising cell-based therapy for Type 1 Diabetes (T1D). The long-term efficacy of this approach, however, is impaired by allorejection. Current clinical practice relies on long-term systemic immunosuppression, leading to severe adverse events. To avoid these detrimental effects, poly(lactic-co-glycolic acid) (PLGA) microparticles (MPs) were engineered for the localized and controlled release of immunomodulatory TGF-β1. The in vitro co-incubation of TGF-β1 releasing PLGA MPs with naïve CD4+ T cells resulted in the efficient generation of both polyclonal and antigen-specific induced regulatory T cells (iTregs) with robust immunosuppressive function. The co-transplantation of TGF-β1 releasing PLGA MPs and Balb/c mouse islets within the extrahepatic epididymal fat pad (EFP) of diabetic C57Bl/6J mice resulted in the prompt engraftment of the allogenic implants, supporting the compatibility of PLGA MPs and local TGF-β1 release. The presence of the TGF-β1-PLGA MPs, however, did not confer significant graft protection when compared to untreated controls, despite measurement of preserved insulin expression, reduced intra-islet CD3+ cells invasion, and elevated CD3+Foxp3+ T cells at the peri-transplantation site in long-term functioning grafts. Examination of the broader impacts of TGF-β1/PLGA MPs on the host immune system implicated a localized nature of the immunomodulation with no observed systemic impacts. In summary, this approach establishes the feasibility of a local and modular microparticle delivery system for the immunomodulation of an extrahepatic implant site. This approach can be easily adapted to deliver larger doses or other agents, as well as multi-drug approaches, within the local graft microenvironment to prevent transplant rejection.